Extremely High Primary Productivity and Organic Matter Enrichment in Lacustrine Sediments: Late Triassic Chang 73 Sub-Member, Western Ordos Basin - Zhiwei Liao; Zigang Wu; Qiang Chen; Yi Zhang; Xiaodong Wang; Yunqian Liu; Zhijie Xu (Geofluids)
The 7th member of the Late Triassic Yanchang Formation is the most important Mesozoic source rocks and shale oil reservoir in the Ordos Basin. The hydrocarbon potential and organic matter enrichment mechanism of this organic-rich member are questioned because of the high heterogeneity of continental sediments. In particular, the lack of drilling in the Chang 73 sub-member of the western Ordos Basin (central Tianhuan Depression) hinders this understanding and the progress of shale oil exploration in this region. In this study, 87 samples were collected from the well DP1 in the Tianhuan Depression, western Ordos Basin, and analyzed for sedimentology and geochemistry to unravel the paleoenvironment, paleo-productivity, and hydrocarbon potential of the Chang 73 sub-member. The results show that the Chang 73 shale is characterized by ultra-high organic matter abundance (up to 10.60%), type II kerogen, and good hydrocarbon generation potential. An intermediate chemical weathering intensity suggests that this set of organic-rich shale was deposited in a warm and humid paleoclimate setting. Extreme organic matter enrichment in study area may be attributed to ultra-high productivity (hypereutrophic lake), superimposed terrigenous organic matter input, and transgression, rather than volcanism and anoxic bottom water. This model is different from those of Chang 73 interval with higher organic matter content in the central and southern parts of the Ordos Basin. Therefore, this study proposes that the Chang 73 shale in the central Tianhuan Depression is not a good target layer for shale oil exploration and that the favorable area may be located in an undisturbed deep lake with higher organic matter abundance (e.g., southwestern Ordos Basin).